2019
DOI: 10.3892/ol.2019.11059
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential pathogenic candidates or diagnostic biomarkers in papillary thyroid carcinoma using expression and methylation profiles

Abstract: The mechanisms underlying the pathogenesis of papillary thyroid carcinoma (PTC) have not yet been elucidated. The aim of the current study was to identify potential pathogenic biomarkers in PTC by comprehensively analyzing gene expression and methylation profiles, and to increase the understanding of PTC pathogenesis. The gene expression profiles of the GSE97001 and GSE83520 datasets, the miRNA expression profiles of the GSE73182 dataset, and the DNA methylation profiles of the GSE86961 and GSE97466 datasets w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In a previous study by Sahin et al, higher serum LDL levels were observed in patients with PTC than those seen in normal volunteers. 40 Given that LDL-receptor-related protein 4 (LRP4) is upregulated in PTC cells, 41 , 42 we hypothesize that the elevated cholesterol influx in tumor cells promotes dedifferentiation. In this study, we also demonstrated that LDL-Ch/TCh was a great biomarker in predicting RAIR-PTC.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study by Sahin et al, higher serum LDL levels were observed in patients with PTC than those seen in normal volunteers. 40 Given that LDL-receptor-related protein 4 (LRP4) is upregulated in PTC cells, 41 , 42 we hypothesize that the elevated cholesterol influx in tumor cells promotes dedifferentiation. In this study, we also demonstrated that LDL-Ch/TCh was a great biomarker in predicting RAIR-PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, MIR100HG repressed the expression of p27 via forming RNA-DNA triplex structure with it and then regulated proliferation and cell cycle progression of breast cancer cells 16 . Moreover, acting as a molecular sponge of miR-204-5p 24 , miR-146b-5p 28 and miR-34a-5p 32 , MIR100HG was able to inhibit their expression and then elevate the expression of their downstream targets. These researches revealed that MIR100HG was able to regulate the expression of downstream targets through diverse mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, miR-199a-5p has been depicted as an inhibitor of progression, cell proliferation, migration, and invasion and a promoter of apoptosis in PTC [ 91 , 142 ]. In addition, it was identified as a potential diagnostic biomarker in this disease [ 143 ]. Turning our attention to follicular thyroid carcinoma, the tumor type corresponding with our CellBox-1 samples, mir-199a-5p, has been reported to act via suppressing connective tissue growth factor (CTGF).…”
Section: Discussionmentioning
confidence: 99%